Ultrasound with neurostimulation compared with ultrasound guidance alone for lumbar plexus block: A randomised single blinded equivalence trial - Vanlapa Arnuntasupakul (2018)
© 2018 European Society of Anaesthesiology. All Rights Reserved. BACKGROUND Ultrasound-guided lumbar plexus blocks usually require confirmatory neurostimulation. A simpler alternative is to inject local anaesthetic inside the posteromedial quadrant of the psoas muscle under ultrasound guidance. OBJECTIVE We hypothesised that both techniques would result in similar total anaesthesia time, defined as the sum of performance and onset time. DESIGN A randomised, observer-blinded, equivalence trial. SETTING Ramathibodi Hospital and Maharaj Nakorn Chiang Mai Hospital (Thailand) from12May 2016 to 10 January 2017. PATIENTS A total of 110 patients undergoing total hip or knee arthroplasty, who required lumbar plexus block for postoperative analgesia. INTERVENTION In the combined ultrasonography-neurostimulation group, quadriceps-evoked motor response was sought at a current between 0.2 and 0.8mA prior to local anaesthetic injection (30 ml of lidocaine 1% and levobupivacaine 0.25% with epinephrine 5μgml -1 and 5mg of dexamethasone). In the ultrasound guidance alone group, local anaesthetic was simply injected inside the posteromedial quadrant of the psoas muscle. MAIN OUTCOMES MEASURES We measured the total anaesthesia time, the success rate (at 30 min), the number of needle passes, block-related pain, cumulative opioid consumption (at 24 h) and adverse events (vascular puncture, paraesthesia, local anaesthetic spread to the epidural space). The equivalence margin was 7.4 min. RESULTS Compared with ultrasound guidance alone, combined ultrasonography-neurostimulation resulted in decreased mean (±SD) total anaesthesia time [15.3 (±6.5) vs. 20.1 (±9.0) min; mean difference, ±4.8; 95% confidence interval,-8.1 to-1.9;P=0.005] andmean (±SD) onset time [10.2 (±5.6) vs. 15.5 (±9.0) min; P=0.004). No inter-group differences were observed in terms of success rate, performance time, number of needle passes, block-related pain, opioid consumption or adverse events. CONCLUSION Although the ultrasonography-neurostimulation technique results in a shorter total anaesthesia time compared with ultrasound guidance alone, this difference falls within our accepted equivalence margin (±7.4 min).